Lessons learned from implementing the pilot Micronutrient Powder Initiative in four districts in Ghana - Kyei-Arthur, Frank (BMC Nutr, 2020)
BACKGROUND: Micronutrient deficiencies affect many children in low-income settings due primarily to over-reliance on complementary foods low in nutrients. Home-fortification (HF) could improve children’s diet quality in these settings. The Ghana Health Service, supported by UNICEF, integrated the pilot Micronutrient Powder Initiative (MPI) into Child Welfare Clinic (CWC) services in four districts (Tain, Tolon, Talensi, and Ho West), whereby micronutrient powder (MNP) is supplied for HF for children aged 6–23 months attending CWCs. This study’s main aim was to identify the facilitators, barriers and “lessons learned” after 2 years of program implementation. METHODS: This was a qualitative cross-sectional study. MNP distributed and children enrolled were obtained from program records. Primary data were collected from November to December 2019 and included, by district: interviews with senior program staff; key informant interviews and focus group discussion with caregivers in each of 6 sub-districts; and discussions workshop with frontline staff from at least 10 health facilities. Besides field notes, all interactions were audio-recorded and transcribed verbatim. Qualitative data were analyzed using NVivo10. RESULTS: The MPI remains on-going, with about 2.5 million MNP sachets distributed to nearly 30,000 children within 90 district-months. Caregivers generally accept the MNP; reported positive responses in children include: “increased appetite”, “less frequent illnesses, “increased energy/strength”, “increased weight”, and “walking independently relatively early”. Main facilitators are: generally regular MNP availability; increased patronage of CWC services; various contact points for supplying MNPs; fairly strong social mobilization strategy; good integration of MPI with CWC services; “one-on-one” counselling for caregivers reporting side effects; and tracing caregivers to address concerns and monitor adherence. Main barriers are: lack of counselling materials; caregivers’ suspicions towards the program; absence of refresher training for frontline workers; and perceived MNP side-effects. Key lessons learned are: incorporating MNPs into CWC services is feasible, acceptable, and could reduce child micronutrient deficiencies in program districts; and MPI’s success requires stronger community sensitization, equipping frontline workers to advise caregivers and manage side-effects, and consciously identifying and managing logistical challenges. CONCLUSION: Further research is needed to evaluate the effectiveness of the MPI in reducing micronutrient deficiencies among 6–23-months-olds in Ghana.